Responsibility of Children's Toys Businessmen against the Hazards of Toys Posed - Umi Hidayati (Unnes Law Journal, 2019)
The aims of this research is to find out and describe the diversity of children’s toys in Semarang City, find out and describe protection in law to children as end user, as well as to find out and describe responsibility of children’s toys businessmen against the hazards of toys posed. The type of this research is qualitative research by using juridical-sociological approachment. The technique of collecting data which was used were literature research, observation, interview, and documentation research. The result of this research show that in Semarang City is not yet known diversity of children’s toys for certain, protection in law for children as end user is not maximal yet, and the responsibility of the businessmen has not been fully implemented or are still limited and conducted unilaterally by the businessmen.